Multimedia Interaktif Pembelajaran Shalat Fardhu Untuk Madrasah Ibtidaiyah Berbasis Android - Sarah Dalila Fitri; Rodia Rotani Rianda; Lara Dwi Alma; Revi Yulianti; Wismanto Wismanto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Students are slow to memorize prayer readings because the learning methods used by teachers are still conventional. As a result, students are not interested in learning prayer readings. The objectives of this research are as follows: (1) create interactive learning media that can be used, easy to use, and suitable for individual learning; and (2) find out how effective the media is in teaching prayer. The Smart App Creator application is used to provide Android-based interactive media. Education must be able to develop the potential of every child in line with current developments in science and technology (IPTEK). Student potential can be developed according to the teacher's ability to manage learning. The material provided must be interesting and not make students bored.